Stylistics of Nida Ilahi and Its Implications in Character Learning - Nursyamsiah, Nunung; Maulani, Hikmah; Khalid, Shofa Musthofa (Universitas Islam Negeri Raden Intan Lampung, 2021)
Nowadays, character learning occupies an important position. There are many studies related to this and the Qur’āncan be a solution in the offer of language and character studies. This study aimed to reveal the way of conveying God (stylistics) to mankind contained in the Qur’ān. A qualitative approach was used with narrative inquiry. The data collection technique was done by analyzing the text of the document which was Al-Maidah verse 90 and 105, also An-Nisa verse 43, which was then analyzed for the data trustworthiness, consistency of research data, the possibility for generalization, neutrality, in a grounded theory research. The results of this study found 3 ways of conveying God to humans in the form of prohibitions or orders, the three appeals are as follows: first, in conveying the order, it is carried out in stages; secondly, the substance conveyed in the message is chosen which is very essential and basic; third, the context chosen is adjusted to the understanding of the aspect. The way God calls His servants with different contexts and appeals can be analyzed so that it is finally adopted as a way of conveying moral messages and character in learning. The results of this study can add to the scientific treasures in character-based language learning.